2018
DOI: 10.1097/ccm.0000000000003402
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Delirium Subtypes in an Adult ICU: A Systematic Review and Meta-Analysis*

Abstract: Objectives: Use systematic review and meta-analytic methodology to estimate the pooled incidence, prevalence, and proportion of delirium cases for each delirium subtype (hypoactive, hyperactive, and mixed) in an adult ICU population. Data Sources: We conducted a search of the MEDLINE, EMBASE, CINAHL, SCOPUS, Web of Science, and PsycINFO databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards from database inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
167
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(189 citation statements)
references
References 51 publications
13
167
1
8
Order By: Relevance
“…“Stereotypical” delirious behaviour was cited in one study (Palacios‐Cena et al, ). This shows a concerning lack of knowledge amongst staff regarding delirium types and manifestations, as hyperactive delirium is the least common presenting state (Krewulak et al, ). Subjective diagnosis of delirium is associated with significant under‐detection (van Eijk, ) and delays the appropriate treatment of underlying causes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…“Stereotypical” delirious behaviour was cited in one study (Palacios‐Cena et al, ). This shows a concerning lack of knowledge amongst staff regarding delirium types and manifestations, as hyperactive delirium is the least common presenting state (Krewulak et al, ). Subjective diagnosis of delirium is associated with significant under‐detection (van Eijk, ) and delays the appropriate treatment of underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…This shows a concerning lack of knowledge amongst staff regarding delirium types and manifestations, as hyperactive delirium is the least common presenting state (Krewulak et al, 2018) However, physical and chemical restraint has been associated with the development or exacerbation of delirium Pan et al, 2018) and therefore does not reflect evidence-based practice. Further research is indicated to explore how unit customs and nurses' perceptions of delirium and agitation impact on restraint use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os principais motivos de causa de internação No grupo de hipertensos estudados, 44,8%fizeram uso de medicamento antihipertensivo na unidade de terapia intensiva geral, sendo mais da metade correspondente à classe dos diuréticos (64,6%). Achado, que pode estar relacionado ao elevado uso de diurético na unidade de terapia intensiva100 , associado ao balanço hídrico positivo, a presença de edema agudo de pulmão e lesão pulmonar aguda em maior porcentagem, seguida da lesão renal aguda e pressão venosa central elevada101 , entre outras causas. ,29 dias.…”
unclassified